2017
DOI: 10.1155/2017/9409145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of C/N on Water State during Composting of Kitchen Waste and Vegetable Waste Mixture

Abstract: The objective of this study was to evaluate the effects of the C/N ratio on the water state changes during the composting of kitchen waste (KW) and vegetable waste (VW) mixtures. The C/N ratios in KW and VW were 50.70 and 27.07, respectively, and the VW was added to the KW to amend the C/N ratio. Five composting treatments were used, R1 with 0% KW, R2 with 25% KW, R3 with 50% KW, R4 with 75% KW, and R5 with 100% KW, and the initial C/N ratios increased in the order R1 < R2 < R3 < R4 < R5. As the composting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In the study done by Karanja et al (2019) initiation of the composting process led to a slight decline of pH upto 6.56 then, it rose gradually to alkaline conditions as high as 10.46 and then gradually decline to almost neutral at the end of composting period to 7.5 to 8.5. Long et al (2017) observed that the initial pH was low with 4.5 to 5.5 than it increased to 7-8.5. In an aerobic dumping of wheat straw treated with microorganisms the initial pH was 5 and as decomposition progressed pH increased upto 8 and the final value was 7 (Pan and Sen, 2013).…”
Section: Aerobic Compostingmentioning
confidence: 91%
See 2 more Smart Citations
“…In the study done by Karanja et al (2019) initiation of the composting process led to a slight decline of pH upto 6.56 then, it rose gradually to alkaline conditions as high as 10.46 and then gradually decline to almost neutral at the end of composting period to 7.5 to 8.5. Long et al (2017) observed that the initial pH was low with 4.5 to 5.5 than it increased to 7-8.5. In an aerobic dumping of wheat straw treated with microorganisms the initial pH was 5 and as decomposition progressed pH increased upto 8 and the final value was 7 (Pan and Sen, 2013).…”
Section: Aerobic Compostingmentioning
confidence: 91%
“…However in the control the rise in temperature was only upto 33.25C due to lesser variation of microbial activities. In different ratios of kitchen waste and vegetable waste composting in aerated reactor, the temperature during thermophilic phase reach upto 55C which gradually declined to 33C in the cooling phase (Long et al, 2017). In the aerated composting done by Guo et al (2012) the rise of temperature was upto 70C from an initial temperature of 25C and in the study done by Fan et al (2016) the initial temperature was 25C which reached upto 52C in the thermophilic stage.…”
Section: Aerobic Compostingmentioning
confidence: 94%
See 1 more Smart Citation